Prospek Pendanaan Proyek Energi Terbarukan di Daerah 3T dengan Skema Digital Crowdfunding - Yulianto, Ahmad Indi; Yusuf, Ahmad Burhanuddin (Prodi Sistem Informasi Universitas Dharma Andalas, 2023)
Development of electricity infrastructure in remote, outermost and underdeveloped (3T) areas requires quite large funds. Generally, 3T areas have abundant renewable energy sources such as sun, wind and other renewable energy sources. Renewable energy projects in rural Indonesia have great potential to provide access to clean energy, improve the quality of life for local communities, and reduce greenhouse gas emissions. Funding constraints are often the main obstacle in moving these projects forward. Crowdfunding has emerged as an effective tool to overcome these obstacles and support the development of renewable energy projects in rural areas. This paper tries to examine the prospects for financing renewable energy projects using digital crowdfunding schemes. By using descriptive methods, we analyze the advantages of this method in mobilizing funds from various sources and analyze the weaknesses of the crowdfunding method for project financing. By conducting studies on several online crowdfunding platforms that already exist in Indonesia and abroad, as well as conducting studies on several renewable energy projects, it can be concluded that digital crowdfunding platforms in Indonesia can be an alternative for project funding, especially the construction of renewable energy plants.